Characterization of the Population of Ovarian Preantral Follicles in Juvenile Six-Banded Armadillos Infected or Not by Mycobacterium leprae - Gabriela L. Lima; Andreza V. Brasil; Andreia M. Silva; João Marcelo A. de P. Antunes; Pierre Comizzoli; Alexandre R. Silva (Veterinary Sciences)
The objective of this study was to characterize and estimate the population of ovarian preantral follicles in juvenile six-banded armadillos. Pairs of ovaries from five armadillos were collected during a routine epidemiological survey of leprosis (three healthy and two infected females). Ovaries weighed approximately 0.06 kg, representing a gonadosomatic index of 6.9 ± 0.8%. The mean ovarian follicular population was 15,567.2 preantral follicles per ovarian pair. For most females, follicular population was mainly composed of primordial follicles. No major histological ovarian parameter was affected by M. leprae infection. All females presented high rates of follicular degeneration, regardless of M. leprae infection. In conclusion, we present original particularities regarding the qualitative and quantitative characteristics of the ovarian population of juvenile six-banded armadillos.